2008
DOI: 10.1121/1.4782816
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in the acoustic expression of emotions in English, German, Hindi, and Arabic.

Abstract: Based on the hypothesis that emotion expression is in large part biologically determined (“universal”), this study examined whether spoken utterances conveying seven emotions (anger, disgust, fear, sadness, happiness, surprise, and neutral) demonstrate similar acoustic patterns in four distinct languages (English, German, Hindi, and Arabic). Emotional pseudoutterances (the dirms are in the cindabal) were recorded by four native speakers of each language using an elicitation paradigm. Across languages, approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research on the coding process has revealed a set of acoustic characteristics that reliably indicate emotions (see next sections for more details; Zei Pollermann & Archinard, ; Scherer, ). The specific acoustic profile of several different emotions, showing similarities across languages, has been established (Hammerschmidt & Jürgens, ; Pell et al ., ). Studies on the decoding process have shown that people are able to extract accurate information about discrete emotions from vocal cues, even across cultures and languages (Scherer, Banse & Wallbott, ; Sauter et al ., ).…”
Section: Vocal Correlates Of Emotions In Humansmentioning
confidence: 97%
“…Research on the coding process has revealed a set of acoustic characteristics that reliably indicate emotions (see next sections for more details; Zei Pollermann & Archinard, ; Scherer, ). The specific acoustic profile of several different emotions, showing similarities across languages, has been established (Hammerschmidt & Jürgens, ; Pell et al ., ). Studies on the decoding process have shown that people are able to extract accurate information about discrete emotions from vocal cues, even across cultures and languages (Scherer, Banse & Wallbott, ; Sauter et al ., ).…”
Section: Vocal Correlates Of Emotions In Humansmentioning
confidence: 97%